Factors Affecting of Price the Fluctuations of Fresh Fruit Bunches in Langkat Regency - Agustian Harianto; Mhd Asaad; Mhd Buhari Sibuea; Faiz Ahmad Sibuea; Mukhlis, Mukhlis (Cita konsultindo, 2024)
The purpose of this study was to determine the effect of Fresh Fruit Bunch production, Crude Palm Oil price and precipitation on Fresh Fruit Bunch prices. The research method used is a qualitative method, where the research was conducted in Langkat Regency. This study uses secondary data, so data collection is done by the documentation method by taking data from related agencies. The data analysis method used is quantitative descriptive analysis method using multiple linear regression analysis. The results showed that the production factors of Fresh Fruit Bunches, Crude Palm Oil prices and rainfall had a significant influence on Fresh Fruit Bunch prices. The finding of this study is that Fresh Fruit Bunch price has a significant influence on fluctuations in Fresh Fruit Bunch price. This study concludes that the factors that have a significant effect on Fresh Fruit Bunch prices are Fresh Fruit Bunch production, Crude Palm Oil prices and rainfall.